Predicting spring phenology in deciduous broadleaf forests: NEON phenology forecasting community challenge - Kathryn I. Wheeler; Michael C. Dietze; David LeBauer; Jody A. Peters; Andrew D. Richardson; Arun A. Ross; R. Quinn Thomas; Kai Zhu; Uttam Bhat; Stephan Munch; Raphaela Floreani Buzbee; Min Chen; et al. (Agricultural and Forest Meteorology, 2024)

Mapped quadrats in sagebrush steppe: long‐term data for analyzing demographic rates and plant–plant interactions - Luke Zachmann; Corey Moffet; Peter Adler (Ecology, 2010)
This historical data set consists of 26 permanent 1‐m 2 quadrats located on sagebrush steppe in eastern Idaho, USA. During most growing seasons from 1923 to 1957, and again in 1973, all individual plants in each quadrat were identified and mapped. This combination of a long time‐series with full spatial resolution allows analyses of demographic processes and intra‐ and interspecific interactions among individual plants. The data provide unique opportunities to test theory about the effect of environmental variation on population and community dynamics and to describe empirical relationships between climate variables and demographic rates. We provide the following data and data formats: (1) the digitized maps in shapefile format; (2) a tabular version of the entire data set (a table with no spatial information except an x,y coordinate for each individual plant record); (3) a species list, containing information on plant growth forms and shapefile geometry type; (4) a record of changes to species names; (5) quadrat information; (6) grazing treatment information; (7) an inventory of the years each quadrat was sampled; (8) monthly precipitation, temperature, and snowfall records; and (9) counts of annuals in the quadrats. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)